Tathbīq Qawāid al-Imlā fī Ta’ lim al-Lughah al-‘ Arabiyyah li ash-Shaff al-Awwal bi Kulliyati al-Mu’ allimīn al-Islāmiyyah fī Ma’hadi Ar-Risālah al-‘Ashri al-Mubarmaj al-‘Alamiy Ponorogo - M Miftah Muttaqin; Kunti Nadiyah Salma; Wahyu Hanafi Putra (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2021)
Arabic writing is a fundamental component of Arabic language learning, as errors in writing may alter the intended meaning of words and sentences. Therefore, mastery of Arabic writing conventions and orthographic rules is essential for developing students’ writing proficiency. At KMI PM Arrisalah Ponorogo, Arabic writing is introduced to first-year students through guided practice and dictation (imla’) activities. This study aims to describe the instructional methods used in teaching Arabic writing, examine the evaluation process, and identify the challenges encountered during the implementation of Arabic writing instruction in Class I of KMI PM Arrisalah Ponorogo. This research employed a qualitative approach using both primary and secondary data sources. The findings indicate that the teaching of Arabic writing is conducted through three main stages: lesson introduction, instructional activities, and lesson closure. Learning evaluation is carried out through the assessment of lesson implementation and students’ writing performance. Several challenges were identified during the instructional process, including students’ low motivation and enthusiasm for learning Arabic writing, teachers’ limited consistency in providing corrective feedback and reminders during classroom activities, and students’ lack of attentiveness, which contributes to writing errors. These findings emphasize the importance of employing effective instructional strategies, continuous feedback, and active classroom engagement to improve students’ Arabic writing skills and reduce orthographic errors.